OBH X Positioning Strategy based on Perceptual Mapping and SWOT Analysis - Wulandari, Sari; Fadoli, Deki Ilham (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
This study aims to describe the right OBH X marketing positioning strategy for the pharmaceutical industry. This study uses a quantitative method. The data sources used in this study are consumers who have consumed at least three brands of cough medicine, OBH X product managers and internal company data. The data collection technique in this study is in the form of a questionnaire dis- tributed to 150 respondents in 3 different regions. The data analysis technique was carried out in a multidimensional and SWOT analysis. Multidimensionality is used to see the brand’s position against competitors. Meanwhile, SWOT anal- ysis is used to identify factors that can be used as a positioning strategy. Based on the results of the research, the positioning strategy applied can be applied to increase OBH X sales in region A by reducing product side effects, adding fla- vor variants and maintaining the efficacy variant of OBH X. Region B of OBH X products cannot be evaluated because there is a gap in predetermined attributes. Meanwhile, in region C, OBH X products are still competing with other prod- ucts. The positioning strategy that can be applied in region C is by maintaining OBH X products using glass bottles, making articles and publishing about the advantages of glass bottle packaging on OBH X products Indonesia.